Analisis Fungsi Kepemimpinan dalam Era Organisasi Modern - Suharti, Suharti; Fajri, Rohmatul; Suharyat, Yayat (LPPM Institut Pendidikan Nusantara Global, 2024)
This research has the main objective of conducting an in-depth analysis of the role and function of leadership in the context of educational institutions, with a focus on improving performance and effectiveness. Through an analytical approach, this research aims to provide a deeper understanding of how leadership influences the dynamics of educational institutions and creates an optimal learning environment. This research identifies leadership practices that are effective in improving the overall quality of teaching, learning, and school management. In addition, this research analyzes the impact of leadership on staff well-being, teacher motivation, and student learning outcomes.The bibliographic method was adopted as the primary approach to collecting and analyzing data, allowing the researcher to detail key concepts and explore recent developments in the educational leadership literature.The research results show that leadership in the context of modern educational institutions is not only related to administrative functions, but also requires adaptation to environmental changes. Leadership functions involving strategic aspects, human resource development, and creating an inclusive organizational culture are the keys to achieving success in educational institutions. The leadership concepts introduced reflect diverse approaches to leading in educational institutions, able to adapt to the unique demands of complexity and dynamics in the world of modern education. Overall, this research contributes to the educational leadership literature and provides insights that educational institution leaders can use to improve and strengthen their role in achieving desired educational goals